ARTIFICIAL INTELLIGENCE-DRIVEN FINANCIAL LITERACY AND IMPROVED START-UP CAPITAL GENERATION AMONG BUSINESS EDUCATION GRADUATES IN UNIVERSITIES IN RIVERS STATE (NAU Journal of Technology and Vocational Education, 2026)
The study determines how artificial intelligence driven financial literacy education relates to improved start-up capital generation among Business Education graduates in universities in Rivers State. Learning is a complex and dynamic process that determines all the activities in the globe today. Two research questions were raised and two hypotheses were formulated. The study employed a correlational research design, with a population of 132 Business Education graduates in universities in Rivers State. This study adopted a census approach, hence there was no sample nor sampling techniques. The researcher’s structured questionnaire titled ‘Artificial Intelligence Driven Financial Literacy Education (AIDFLE) Questionnaire and Improved Start-up Capital Generation (ISUCG) Questionnaire   The research instruments were reviewed and validated by three experts Out of the 132 copies of the instrument distributed 129 were properly filled, retrieved and used for analysis of the study. The research questions and hypotheses were analyzed with the use of Regression statistical tool to ascertain the relationship between the variables. Based on the finding, the study revealed that the two research questions show a correlation coefficient of .189 and .207 on how AI-driven financial literacy relates to improves start-up capital generation. This means that there is a high positive relationship between AI-driven financial literacy and start-up capital generation in Universities in Rivers State. Hypothesis 1 and 2 were not retained because the ‘F’ calculated values had associated probability value is lesser than 0.05 level of significance, meaning that AI driven financial literacy education of crowdfunding and angel investors has a positive significant relationship with start-up capital generation. It was recommended among others that administrators should organise training and workshops on AI-driven crowdfunding investment decision tools as well as encourage AI Research in financial literacy, with involvement of angel investors in full participation in start-up capital.
Keywords: Artificial Intelligence; Financial literacy; Angel investors; crowdfunding; start-up capital